The analysis of methodological foundations for optimal design of gas transmission information systems - K. A. Ankudinov; K. S. Khalikova (Омский научный вестник)
An analysis is carried out on the problem of creating methodological foundations for the optimal construction of information technologies that provide integrated logistics support for the life cycle of gas transmission system samples with uncertainty of the initial data. The analysis of the state of research of the problems of analysis, synthesis and forecasting of the development of complex.